Occasionally increased 18F-fluorodeoxyglucose uptake in apical hypertrophic cardiomyopathy with mid-ventricular obstruction. Issue 2 (August 2017) - Yamamoto, Hideya; Kitagawa, Toshiro; Susawa, Hitoshi; Hata, Ryoichiro; Tatsugami, Fuminari; Higaki, Toru; Awai, Kazuo; Kihara, Yasuki
Abstract: We report on a 77-year-old man who was diagnosed with apical hypertrophic cardiomyopathy (HCM) with mid-ventricular obstruction. He had a cured hepatitis C infection. We detected occasionally increased 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake on whole-body positron emission tomography (PET)/computed tomography (CT) performed to examine the involvement of bladder carcinoma. 18 F-FDG-PET was restudied following specific preparation involving an 18-h low-carbohydrate diet and following 15-h fasting plus heparin pre-administration. Increased uptake of 18 F-FDG was observed reproducibly in the hypertrophic apical to mid left ventricular myocardium, with a maximum standardized uptake value of 6.2. In contrast, relatively lower 18 F-FDG-uptake areas tended to match areas of late gadolinium enhancement on cardiac magnetic resonance (CMR). Histopathological examination of myocardial biopsy showed disarried hypertrophic myocytes with cellular infiltration. Increased uptake of 18 F-FDG may reflect the phenomenon of increased glucose utilization in hypertrophied myocardium. The increasing clinical utility of whole-body PET/CT for evaluating malignancies may increase the detection of occasional abnormal 18 F-FDG uptake in the heart. It is necessary to clarify that 18 F-FDG myocardial PET in combination with CMR may provide a more detailed risk assessment in patients with HCM. <Learning objective: Increased 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake was occasionally found in the apex of the heart on whole-body positron emission tomography performed to evaluate bladder cancer involvement. Increased uptake of 18 F-FDG was observed in the hypertrophic apical to mid left ventricular myocardium, while relatively lower 18 F-FDG-uptake areas tended to match areas of late gadolinium enhancement.>